Effects of Prefrontal Transcranial Direct Current Stimulation on Lexical Access in Chronic Poststroke Aphasia. (October 2018) - Pestalozzi, Maria I.; Di Pietro, Marie; Martins Gaytanidis, Chrisovalandou; Spierer, Lucas; Schnider, Armin; Chouiter, Leila; Colombo, Françoise; Annoni, Jean-Marie; Jost, Lea B.
Background . A successful interplay between prefrontal and domain-specific language areas is critical for language processing. Previous studies involving people with aphasia have shown that executive control processes might act on lexical-semantic representations during retrieval. Modulating the prefrontal control network by means of noninvasive brain stimulation might, therefore, improve lexical access in people with aphasia. Objective . The present study investigates the effects of prefrontal transcranial direct current stimulation (tDCS) on lexical access in chronic poststroke aphasia. Methods . We report data of 14 participants with chronic poststroke aphasia. We used a sham-tDCS (S-tDCS) controlled and double-blind within-subjects design. Performances in picture naming, verbal fluency, and word repetition were assessed immediately after stimulation. Results . As compared with S-tDCS, anodal tDCS (A-tDCS) improved verbal fluency as well as the speed of naming high frequency words, but not word repetition. Conclusion . The results of our study suggest that the brain network dedicated to lexical retrieval processing can be facilitated by A-tDCS over the left dorsolateral prefrontal cortex. This finding supports the notion that strengthening executive control functions after stroke could complement speech and language-focused therapy.